IJAR 2019
DOI: 10.21474/ijar01/8900
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prior Work Experience on Entrepreneurial Intention and Theory of Planned Behavior in Context of Pakistan.

Abstract: The present study aims to investigate the impact of prior work experience influence on the entrepreneurial intention in the context of Pakistan. Where 58% population lies in the age of 20-30 years, 45 % people hold master degree. 58% people have experience in private firms. The sample of 438, represents the population of Pakistan. Study used the partial least square structural equation modelling software (PLS-SEM) 3.2.7, and the techniques used involves PLS Algorithm, Bootstrapping, scales used witnessed by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The ndings in this study indicate that years of practice are negatively associated with EI among dentists in China, holding other factors constant. Given a small group of literature reporting the decline in selfemployment among near-retirees [63], most literature studying general business reports positive associations between working experience and EI [64][65][66]. Actually, the ndings in this study have reasonably re ected the professional feature of dentistry.…”
Section: Discussionmentioning
confidence: 56%
“…The ndings in this study indicate that years of practice are negatively associated with EI among dentists in China, holding other factors constant. Given a small group of literature reporting the decline in selfemployment among near-retirees [63], most literature studying general business reports positive associations between working experience and EI [64][65][66]. Actually, the ndings in this study have reasonably re ected the professional feature of dentistry.…”
Section: Discussionmentioning
confidence: 56%
“…The ndings in this study indicate that years of practice are negatively associated with the EI among dentists in China, holding other factors constant. Given a small group of literature reporting the decline in self-employment among near-retirees [56], most literature studying general business reports positive associations between working experience and EI [57][58][59]. Actually, the ndings in this study have reasonably re ected the professional feature of dentistry.…”
Section: Discussionmentioning
confidence: 57%
“…Current literature provides support for the positive relationship between working experience and EI [48,49,89,107,108]. Furthermore, Fatoki [109] showed that students with previous work experience (PWE) have a higher level of EI compared to those without.…”
Section: Research Framework and Hypothesis Developmentmentioning
confidence: 95%